¿Todos los ‘hombres’ del Presidente?: Una mirada al Poder Ejecutivo a propósito de los ministros y ministras en el Perú post-Fujimori (2001-2014) - Sosa Villagarcia, Paolo (2014)
This paper focuses on ministers as government executives, paying special attention tothe case of Peru after the fall of Alberto Fujimori’s rule. This exploratory perspective seeks to provide a look over the political and technical characteristics of these executive corps in recent governments as well as the variation in their stability. In that sense, the purpose of this paper is (1) to describe their demographic and professional characteristics; and (2) analyze some indicators of ministerial stability and cabinet configuration. For this purpose a database of ministers (1990- 2014) is used, focusing the analysis in democratically elected governments after Fujimori (2001-2014).